Hubungan Kejadian Bullying dengan Gangguan Tidur pada Siswa SMA Negeri 1 Kuta Utara - I Putu Satyawan Rama Natha; Putu Asih Primatanti; Ni Putu Diah Witari (Aesculapius Medical Journal, 2024)
[Correlation between Bullying and Sleep Disorder in students of SMA Negeri 1 Kuta Utara] Bullying often occurs in the school environment. Physical and non-physical bullying behavior will have an impact on emotional, social, physical, and psychological. The purpose of this research is to find out the relationship between bullying and sleep disorders for students of SMA Negeri 1 Kuta Utara. This research is an analytical type with a cross-sectional approach. The sample was determined by a simple random sampling method of 104 people. The implementation will be carried out in February-May 2024. Data analysis using Chi-Square showed a total p< 0.05 (0.046) which means that there is a link between bullying and student sleep disorders. Students are expected to participate in bullying prevention efforts in schools and further research is expected to examine other factors that affect the relationship between bullying incidents and sleep disorders.